PLANNING OF CONSTRUCTION MANAGEMENT FOR THE IMPLEMENTATION OF 3 FLOOR FLAT HOUSE OF SEMINARI SANTA YOHANES MARIA VIANNEY KEUSKUPAN SINTANG, SINTANG DISTRICT, WEST BORNEO: Construction Management, Cost Management, Time, Human Resource, Quality, and Occupational Safety and Health, Sintang City. - Tasari, Devi Devita; sari, Dhevita Maytika; fitriani, nurul (RETENSI, 2021)
Sintang Region has few Catholic priests and does not have sufficient accomodation for the Catholic priesthood candidates. Therefore, a plan for a three floored Flat House of Santa Yohannes Maria Vianney Seminary of Sintang Diocese in Teluk Menyurai road, was proposed. It is expected that the seminary which may be built based on the plan, will be able to produce high quality Human Resources in Sintang Region expecially for the priesthood candidates and also to provide accomodation for them. Construction Management is a project processing process that includes planning, and organizing for purpose to be achived. To fulfill the requirements of Final Diploma 4 at State Polytechnic of Pontianak, we took the concept of Construction Management as a Final Project.Our Final Project includes Cost Management to find out the details of project costs in the form of a Budget Plan (RAB), Time Management to determine project duration in the form of S-curve and Critical Path Method (CPM), Human Resource Management to find out the needs of power workers in the form of a Tabel of The Needs of Power Workers, Quality Management to find out the specifications and provisions in the project structure that compile the specification table and Work Plan and Requirements (RKS),andOccupational Safety and Health (SMK3)Management to find the dangers and risks that may occur at the project in the form table of K3. In our plan, the SNI was applied to determine RAB and the result was Rp 7,791,782,000 and the build time needed was 120 days. The Human Resource per work item per day was also determined. This study also figured out the quality of the building structure, the risks and how to overcome and prevent the risks.